1992
DOI: 10.1002/j.2050-0416.1992.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

ELECTROPHORETIC STUDY OF SUBSTRATE AND pH DEPENDENCE OF ENDOPROTEOLYTIC ENZYMES IN GREEN MALT*

Abstract: The endoproteolytic enzymes of malt influence several different aspects of malt and beer quality. For this reason, we are extracting and characterizing these enzymes from green malt. The proteolytic activity of a Morex green malt extract was highest at pH 3.8 with haemoglobin substrate but gelatin hydrolysis was maximal from pH 4.7 to 6.0. Endoproteolytic hydrolysis of a 55% isopropanol-soluble reduced hordein fraction was about three times slower than gelatin hydrolysis but was relatively constant over the pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Typically, 100 g of material was homogenized in 0.05 M sodium acetate buffer, pH 4.7, containing 2 mm cysteine and 1 mM EDTA and centrifuged, and the supernatant was dialyzed against 5 mm sodium acetate buffer at pH 5.0 as described previously (29). This 'crude extract' was frozen in 0.5-mL portions and stored at -200C.…”
Section: Preparation Of Germinating Barley Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, 100 g of material was homogenized in 0.05 M sodium acetate buffer, pH 4.7, containing 2 mm cysteine and 1 mM EDTA and centrifuged, and the supernatant was dialyzed against 5 mm sodium acetate buffer at pH 5.0 as described previously (29). This 'crude extract' was frozen in 0.5-mL portions and stored at -200C.…”
Section: Preparation Of Germinating Barley Extractsmentioning
confidence: 99%
“…We recently concluded a study using electrophoresis with nondenaturing gels containing incorporated substrate proteins that revealed that there were seven proteolytic activity bands in a crude green malt (4-d-germinated barley) extract (29). Five of the endoproteinase bands were maximally active at pH 3.8, and the other two were maximally active at pH 5.5 to 6.5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They were shown to hydrolyse hordein and their formation was shown to be induced by gibberellin during germination. All these purifications were based on the use of non-barley protein substrates, such as casein, haemoglobin and gelatin for the detection and assay of the purified enzymes 2,3,9,18,19,22 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…However, the latter could not be confirmed at lower concentrations of the inhibitor. This flies in the face of the most widely reported conclusion, which stipulates that the most active, at acidic pH, green malt endoproteases are cysteine class endoproteases [2][3][4][5][6][7]9,10,17,21,22 . It is very important to note that our enzymes were purified from malt rather than green malt, which is very commonly used.…”
Section: 'Levegxivmwexmsr Sj XLI Jmzi Tevxp] Tyvmjmih Irhstvsxiewiwmentioning
confidence: 99%